Estrogen receptor mediated activity in bankside groundwater, with flood suspended particulate matter and floodplain soil – An approach combining tracer substance, bioassay and target analysis - Wölz, J.; Grosshans, K.; Streck, G.; Schulze, T.; Rastall, A.; Erdinger, L.; Brack, W.; Fleig, M.; Kühlers, D.; Braunbeck, T.; Hollert, H. (Chemosphere (Oxford), 2011)
► First-time investigation of flood impact on groundwater/drinking water resources. ► Tracer substance analysis marked deep infiltration of flood water into groundwater. ► Detection of estrogenic activity supported this finding. ► High relevance for drinking water supply safety and groundwater protection. ► Indicates further focuses to reach aims of European Water Framework Directive. Bankside groundwater is widely used as drinking water resource and, therefore, contamination has to be avoided. In the European Union groundwater protection is explicit subject to Water Framework Directive. While groundwater pollution may originate from different sources, this study investigated on impacts via flood events. Groundwater was sampled with increasing distance to the river Rhine near Karlsruhe, Germany. Samples were HPLC–MS–MS analyzed for the river contaminant carbamazepine to indicate river water infiltration, giving permanent presence in 250 m distance to the river (14–47 μg L −1). Following a flood event, concentrations of about 16–20 μg L −1 could also be detected in a distance of 750 m to the river. Furthermore, estrogenic activity as determined with the Yeast Estrogen Screen assay was determined to increase up to a 17β-ethinylestradiol equivalent concentration (E-EQ) = 2.9 ng L −1 near the river, while activity was initially measured following the flood with up to E-EQ = 2.6 ng L −1 in 750 m distance. Detections were delayed with increasing distance to the river indicating river water expansion into the aquifer. Flood suspended matter and floodplain soil were fractionated and analyzed for estrogenic activity in parallel giving up to 1.4 ng g −1 and up to 0.7 ng g −1, respectively. Target analysis focusing on known estrogenic active substances only explained <1% of measured activities. Nevertheless, river water infiltration was shown deep into bankside groundwater, thus, impacting groundwater quality. Therefore, flood events have to be in the focus when aiming for groundwater and drinking water protection as well as for implementation of Water Framework Directive.